Improving the Competence of Junior High School Teachers In Designing Instructional Media to Facilitate Flexible Learning - Novitra, Fuja; Anshari, Rio; Fitri, Bali Yana; Suherman, Dea Stivani (Fakultas MIPA Universitas Negeri Padang, 2024)
Learning has undergone a significant transformation in recent years. Technological advances have made it possible to use various digital platforms to support learning [1], [2]. In this era, the phenomenon of learning flexibility has become a top priority for educational institutions in various countries [3]. Flexible learning will help increase the effectiveness of learning and help students develop skills that are relevant to an increasingly complex world of work [4]. Learning flexibility in the era of digital technology in science education does not only include a combination of online or offline learning [5], but must also have a pedagogical framework that is oriented towards a balance of digital experience and scientific experience [6] [7] [8]. To achieve a balanced combination of digital and scientific experiences, teachers need to provide relevant resources, including interactive digital platforms and scientific tools. In addition, teachers must plan and implement practical activities that involve students in direct experience in the real world. To accommodate this, teaching materials are needed that implement a learning framework that integrates constructivist learning theory with connectivistic learning theory [9] [10] [11], so that science learning supported by various digital platforms can be more effective.However, conditions in the field show that the majority of teachers have not been able to implement this flexible learning framework and develop their teaching materials. Based on early observations at junior high schools in Agam Regency that the Community Service Team has carried out, the percentage of teachers who are able to implement the learning framework is only around 10%. The lack of socialization from the government and academics regarding the implementation of flexible learning frameworks in the digital era has also resulted in the low ability of junior high school science teachers in Agam Regency to be able to develop teaching materials that are able to facilitate flexible learning in the era of digital technology (only around 5%).The Community Partnership Program (PKM) in the form of Mentoring MGMP Science Teachers in Agam Regency in Developing Teaching Materials to facilitate Flexible Learning in the Digital Technology Era is a solution that needs to be implemented. The ultimate goal of this assistance is to increase teacher readiness to implement the flexible learning framework and develop teaching materials. The results of mentoring activities show that the final competency level achieved was 81% and digital teaching material products were obtained.